Respuesta :

Answer:

Let's solve your equation step-by-step.

-2/3 (x+12)+2/3x=-5/4x+2

Step 1: Simplify both sides of the equation.

−2/3 (x+12)+2/3x=−5/4x+2

(−2/3)(x)+(−2/3)(12)+2/3x=−5/4x+2(Distribute)

−2/3x+−8+2/3x=−5/4x+2

(-2/3x+2/3x)+(−8)=−5/4x+2(Combine Like Terms)

−8=−5/4x+2

−8=−5/4x+2

Step 2: Flip the equation.

−5/4x + 2=−8

Step 3: Subtract 2 from both sides.

−5/4x+2−2=−8−2

−5/4x=−10

Step 4: Multiply both sides by 4/(-5).

(4/-5)×(-5/4x)=(4/-5) ×(-10)

Answer: X = 8

ACCESS MORE